Exploring students' performances in implementing social strategy during online learning - Sumarni; Aries Utomo (Center for Humanities and Innovation Studies, 2021)
Many scholars have studied the Covid 19 epidemic and online-based courses on English lectures using inventive good strategy mapping. Using two online platforms, this study investigated the social practices in learning English as a foreign language. The research method used in this study is a quantitative descriptive method with fifty students from two different study programs: 1) Department of Dentistry, Faculty of Medicine, Universitas Mulawarman; 2) Public Administration Study Program, Faculty of Social and Political Sciences, University of 17 Augustus 1945 Samarinda. A quantitative description was used in this study, followed by an in-depth conversation with a sample of the existing population. The study's findings provide an overview of the usage of social techniques in learning English, with the two groups of students favoring the other five tactics. This research also shows how the two groups of respondents apply various aspects of the technique. The findings of this study are expected to be valuable to teachers and curriculum creators when it comes to setting up cooperative learning online. As part of constructive learning, social strategy is one of the strategies that support our learning style. It should be treated at any English level, rather than achieving learner capacity in English through group discussion. This study should be encouraged to everyone through added study with the same previous activities.